COMMUNION FOR THE DIVORCED AND REMARRIED? - Wales, Sean (Asian Horizons, 2013)
In what seems like a final “testament” Cardinal Martini offered three vital elements in the renewal of tired old Church of Europe: Conversion, the Word of God and the Sacraments. Speaking of the Sacraments he clothed his words in a vivid example: A woman, for instance, is abandoned by her husband and finds a new companion, who takes care of her and her three children. This second love succeeds. If this family is discriminated against, not only is the mother cut out [from the Church] but also her children. If parents feel that they’re outside the Church, and don’t feel its support, the Church will lose the future generation.